The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1186/1471-244x-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Mental health first aid responses of the public: results from an Australian national survey

Abstract: Background: The prevalence of mental disorders is so high that members of the public will commonly have contact with someone affected. How they respond to that person (the mental health first aid response) may affect outcomes. However, there is no information on what members of the public might do in such circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 16 publications
9
98
1
2
Order By: Relevance
“…Several previous studies with an adult sample have identified that professional help is less likely to be recommended when the respondent does not correctly identify the disorder in the vignette (Jorm et al, 2005;Reavley and Jorm, 2011;Rossetto et al, 2014b). This was replicated with the adolescent sample in the current study; correct recognition of the problem in the vignettes significantly predicted scoring on the Help them connect with an adult step of the action plan.…”
Section: Predictors Of First Aid Qualitysupporting
confidence: 71%
See 1 more Smart Citation
“…Several previous studies with an adult sample have identified that professional help is less likely to be recommended when the respondent does not correctly identify the disorder in the vignette (Jorm et al, 2005;Reavley and Jorm, 2011;Rossetto et al, 2014b). This was replicated with the adolescent sample in the current study; correct recognition of the problem in the vignettes significantly predicted scoring on the Help them connect with an adult step of the action plan.…”
Section: Predictors Of First Aid Qualitysupporting
confidence: 71%
“…found that adolescent males are less likely than females to encourage professional help-seeking, more likely to recommend self-help strategies, and less likely to provide general support. In an adult sample, encouraging professional help was less likely to be reported by males, respondents with higher levels of personal stigma towards those with a mental health problem, and respondents unable to correctly identify the problem in the vignette (Jorm et al, 2005). Higher personal stigma was also associated with a lower likelihood for listening/talking/supporting, and giving information about the problem (Jorm et al, 2005).…”
Section: Introductionmentioning
confidence: 78%
“…These are related to educational mental health literacy workshops, such as the Mental Health First Aid Kit (Jorm et al, 2005(Jorm et al, , 2007(Jorm et al, , 2010a, which aims to raise the general level of knowledge about mental health and how to improve it; or interventions to promote the mental wellbeing of the elderly, regardless of their health status, focusing on life skills and the promotion of social networks (Forsman et al, 2011). Maybe the more realistic strategy is to enrich the health promotion activities focused on physical activity, healthy diet, or reduction of alcohol intake or smoking with activities targeting self-esteem and self-efficacy (Kelly et al, 1991); another options could be to promote mental health by social prescription activities (see the review by March in this supplement).…”
Section: Discussionmentioning
confidence: 99%
“…The empirical literature demonstrates a relationship between incontinence and mental illness (Avery et al, 2013b;Heymen, 2004), and that mental health is associated with a reduction in helpseeking (Hahm & Segal, 2005;Jorm, Blewitt, Griffiths, Kitchener & Parslow, 2005;Mojtabai, Olfson & Mechanic, 2002). However, research which explicitly focuses on the psychological implications of incontinence has been minimal, mostly concentrating on older people, women and/or samples of convenience (Black, Griffiths, Pope, Bowling & Abel, 1997;Chiarelli & Cockburn, 2002;Heidrich & Wells, 2004).…”
Section: Introductionmentioning
confidence: 95%